2013
DOI: 10.1136/bmjopen-2013-002826
|View full text |Cite
|
Sign up to set email alerts
|

Health risk factors and the incidence of hypertension: 4-year prospective findings from a national cohort of 60 569 Thai Open University students

Abstract: ObjectiveThis study evaluates the impact of a number of demographic, biological, behavioural and lifestyle health risk factors on the incidence of hypertension in Thailand over a 4-year period.DesignA 4-year prospective study of health risk factors and their effects on the incidence of hypertension in a national Thai Cohort Study from 2005 to 2009.SettingAs Thailand is transitioning from a developing to a middle-income developed country, chronic diseases (particularly cardiovascular disease) have emerged as ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 91 publications
(98 reference statements)
5
48
0
2
Order By: Relevance
“…Although the trend of cigarette smoking in Thai men is declining its prevalence still exceeds 20% overall and reaches 40% in some groups (Kamsa-ard, 2013;Zhao, Pachanee, et al, 2015). Regular smoking is directly associated with a higher incidence of hypertension (Thawornchaisit et al, 2013c). The traditional expectation that females do not smoke continues to powerfully protect half of the population from tobacco related illness, including hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the trend of cigarette smoking in Thai men is declining its prevalence still exceeds 20% overall and reaches 40% in some groups (Kamsa-ard, 2013;Zhao, Pachanee, et al, 2015). Regular smoking is directly associated with a higher incidence of hypertension (Thawornchaisit et al, 2013c). The traditional expectation that females do not smoke continues to powerfully protect half of the population from tobacco related illness, including hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The study participants live all over Thailand and represent people well socio-demographically (Seubsman et al, 2012) even though they are younger and have a higher education attainment than average for general population. A previous 4-year follow up study in 2009 (Thawornchaisit et al, 2013c) and associated 2005 baseline cross-sectional study (Thawornchaisit et al, 2013a) identified risk factors for hypertension in Thai people. But the results of this 8-year study will be more accurate despite losing some statistical power due to cohort attrition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…more one-person or couple-with-no-children households). Health and other social outcomes of urbanisers were closer to those in the urban-urban group and were worse than the rural-rural group, with lower self-assessed health and a higher prevalence of hypertension, depression and obesity Seubsman et al, 2010Seubsman et al, , 2011Thawornchaisit et al, 2013).…”
Section: Key Research Findingsmentioning
confidence: 92%